Stenting of the left pulmonary artery after palliation of hypoplastic left heart syndrome. Issue 2 (24th February 2016) - Noonan, Patrick; Kudumula, Vikram; Anderson, Ben; Ramchandani, Bharat; Miller, Paul; Dhillon, Rami; Mehta, Chetan; Stumper, Oliver
Abstract : Background: Left pulmonary artery stenosis and hypoplasia is a well‐recognized complication following surgical palliation of hypoplastic left heart syndrome. These lesions produce increased after load in a circulation in series so need to be effectively treated. Methods: Between 2000 and 2011, 86 patients after surgical palliation for hypoplastic left heart syndrome had left pulmonary artery stents implanted. Median age at implantation was 4.7(1.3–15.2) years and median weight was 16.4(9.3–55.2) kg. Uncovered peripheral vascular stents were implanted (median diameter 10(8–15) mm). This is a retrospective review of the incidence of in‐stent restenosis over the medium to long term. Results: During primary stenting procedures, there were 2/88(2.3%) major complications of stent migration with no stroke or mortality. Follow‐up was for a median period of 4.1(0.5–13.4) years. Follow‐up catheter procedures were performed after a median time of 2.3(0.02–9.6) years in 59 patients (68.6%). 55/59(93.2%) had at most mild restenosis (≤10% loss of stent lumen) and 47/59(79.6%) had no evidence of any restenosis at all caused by neointimal in‐growth. Freedom from reintervention was 77% at 5 years including stent dilation to compensate for somatic growth. Freedom from reintervention for restenosis was 93% at 5 years. Restenosis was successfully treated with standard balloon angioplasty or restenting. There was only 1/94 (1.1%) major complication in the follow‐up catheterizations of stent embolization with successful transcatheter retrieval. Conclusions: Stenting of the left pulmonary artery after Norwood/Fontan palliation is safe and effective. Stents can be redilated to match somatic growth. The incidence of neointimal proliferation is extremely low and can be addressed by balloon dilation or stent implantation. © 2016 Wiley Periodicals, Inc.